Herb Schildt's C++ programming cookbook - Schildt, Herbert (McGraw-Hill's AccessEngineering., 2008)
This title is new from the world's number-one programming author. In this book, bestselling programming author Herb Schildt provides more than 200 practical, self-contained recipes for experienced C++ programmers. Each chapter contains a series of real-life programming tasks, followed by code solutions and concise but detailed discussions on the technique used. This guide will be essential to every C++ programmer's toolkit.